Inclusiveness, Equity, Consistency, and Flexibility as Guiding Criteria for Enabling Transdisciplinary Collaboration: Lessons From a European Project on Nature-Based Solutions and Urban Innovation - Basta, Claudia; Kunseler, Eva; Wamsler, Christine; van der Jagt, Alexander; Baró, Francesc; Balenciaga, Intza; Bach, Matthew; Wickenberg, Björn (Frontiers in Climate, 2021)
The structural research programmes of the European Union dedicated to advance the sustainability sciences are increasingly permeated by the notion of transdisciplinarity (TD). A growing body of literature residing at the intersection of research methodology and sustainability studies can guide researchers to adopt appropriate research approaches in their projects. However, how to implement the transdisciplinary approach in multidisciplinary and multi-stakeholder projects that develop in different countries for several years is still relatively undocumented. This study seeks to fill this gap by sharing the experience of a group of researchers and stakeholders involved in the Horizon 2020 research and innovation project Nature-Based Urban Innovation (NATURVATION). The article discusses the monitoring and evaluation strategy that employed four criteria of transdisciplinary research quality as ‘reflexive devices’ to enable a systematic reporting on the project’s most important collaborative activities. By examining how the four criteria captured transdisciplinary quality, new insights were produced for improving this monitoring and evaluation strategy for future transdisciplinary research, allowing a number of concrete recommendations to be formulated.